Novel bisphosphonate-based cathepsin K-triggered compound targets the enthesis without impairing soft tissue-to-bone healing - Shi, Brendan Y.; Sriram, Varun; Wu, Shannon Y.; Huang, Dave; Cheney, Alexis; Metzger, Melodie F.; Sundberg, Oskar; Lyons, Karen M.; McKenna, Charles E.; Nishimura, Ichiro; Kremen, Thomas J. (Frontiers in Bioengineering and Biotechnology, 2024)
1. Abstract 1.1 Background Osteoadsorptive fluorogenic sentinel 3 (OFS-3) is a recently described compound that contains a bone-targeting bisphosphonate (BP) and cathepsin K (Ctsk)-triggered fluorescence signal. A prior study in a murine Achilles repair model demonstrated its effectiveness at targeting the site of tendon-to-bone repair, but the intrinsic effect of this novel bisphosphonate chaperone on tendon-to-bone healing has not been previously explored. We hypothesized that application of this bisphosphonate-fluorophore cargo conjugate would not affect the biomechanical properties or histologic appearance of tendon-bone repairs. 1.2 Materials and Methods Right hindlimb Achilles tendon-to-bone repair was performed on 12-week old male mice. Animals were divided into 2 groups of 18 each: (1) Achilles repair with OFS-3 applied directly to the repair site prior to closure, and (2) Achilles repair with saline applied prior to closure. Repaired hindlimbs from 12 animals per group were harvested at 6 weeks for biomechanical analysis with a custom 3D-printed jig. At 4 and 6 weeks, repaired hindlimbs from the remaining animals were assessed histologically using H&E, immunohistochemistry (IHC) staining for the presence of Ctsk, and second harmonic generation (SHG) imaging to evaluate collagen fibers. 1.3 Results At 6 weeks, there was no significant difference in failure load, stiffness, toughness, or displacement to failure between repaired hindlimbs that received OFS-3 versus saline. There was no difference in tissue healing on H&E or Ctsk staining on IHC between animals that received OFS-3 versus saline. Finally, SHG imaging demonstrated no difference in collagen fiber parameters between the two groups. 1.4 Conclusion OFS-3 did not significantly affect the biomechanical properties or histologic appearance of murine Achilles tendon-to-bone repairs. This study demonstrates that OFS-3 can target the site of tendon-to-bone repair without causing intrinsic negative effects on healing. Further development of this drug delivery platform to target growth factors to the site of tendon-bone repair is warranted.